Austerity in 2009–13. (30th July 2015) - Alesina, Alberto; Barbiero, Omar; Favero, Carlo; Giavazzi, Francesco; Paradisi, Matteo
Abstract: The conventional wisdom is (i) that fiscal austerity was the main culprit for the recessions experienced by many countries, especially in Europe, since 2010 and (ii) that this round of fiscal consolidation was much more costly than past ones. The contribution of this paper is a clarification of the first point and, if not a clear rejection, at least it raises doubts on the second. In order to obtain these results we construct a new detailed "narrative" dataset which documents the size and composition of the fiscal plans implemented by several countries over 2009–13. Out of sample simulations, that project output growth conditional only upon the fiscal plans implemented since 2009, do reasonably well in predicting the total output fluctuations of the countries in our sample over the years 2010–13 and are also capable of explaining some of the cross-country heterogeneity in this variable. Fiscal adjustments based on cuts in spending appear to have been much less costly, in terms of output losses, than those based on tax increases. Our results, however, are mute on the question whether the countries we study did the right thing implementing fiscal austerity at the time they did, that is 2009–13.